UNIT KEGIATAN MAHASISWA DAN PERANNYA DALAM MEMBENTUK KARAKTER MAHASISWA (Studi Kasus di Unit Kegiatan Mahasiswa Jam’iyyah al-Qurra’ wa al-Huffazh Al-Furqan Institut Agama Islam Negeri Salatiga) - Tri Hartono (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
In the institute environment to achieve educational objectives the role of Student Activity Unit is needed especially in the development of talent, interest and character formation of students. Like the Jam’iyyah al-Qurra’ wa al-Huffazh (JQH) Al-Furqan of Institut Agama Islam Negeri (IAIN) Salatiga who developed it all through the art of the Quran. Thus, the objective to be achieved in this research is to know the character of JQH Al-Furqan member and the role of JQH Al-Furqan in shaping the character of IAIN Salatiga student. This research is a type of field research and descriptive qualitative. Sources of data in this study include primary sources and secondary sources. Data collection is done by observation, interview, and documentation. Validity of data obtained through triangulation, collected data sources are analyzed by data reduction, data presentation, and verification. The result of the journal shows that (1) the character of JQH Al-Furqan of IAIN Salatiga members are: religious, tolerance, discipline, creative, unyielding, honest, caring, curiosity, friendly and hard work; (2) JQH Al-Furqan in the formation of student character in IAIN Salatiga is through various programs of work, among others are: acceptance of new members, workshop members and management, sima'an al-Qur'an, weekly training Rebana, weekly calligraphy exercise, weekly exercise Tilawah al-Qur'an, weekly Tafsir review, Tahfizh al-Qur'an programme, weekly management meeting, national Tahfizh workshop, and gebyar art of Quran (Central Java) level.